2021
DOI: 10.3390/nu14010031
|View full text |Cite
|
Sign up to set email alerts
|

Too Jittery to Sleep? Temporal Associations of Actigraphic Sleep and Caffeine in Adolescents

Abstract: Caffeine consumption has been linked to poor sleep health in adolescents, but it is unknown whether poor sleep predicts caffeine consumption, and/or whether caffeine consumption predicts poor sleep, particularly when sleep is measured objectively. Data were collected from a micro-longitudinal sub-study of the age 15 wave of the Fragile Families and Child Wellbeing Study (n = 589). Adolescents wore an actigraphy device and completed daily surveys for ~1 week. Daily surveys assessed subjective sleep quality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…A vicious circle could accordingly be established where ED consumption leads to less sleep which then again entails increasing ED consumption resulting from tiredness. This is plausible and in line with other studies when considering the caffeine content in ED and its known effects on sleep [ 10 , 13 ]. In addition, the association found in our study suggests a dose-response relationship.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A vicious circle could accordingly be established where ED consumption leads to less sleep which then again entails increasing ED consumption resulting from tiredness. This is plausible and in line with other studies when considering the caffeine content in ED and its known effects on sleep [ 10 , 13 ]. In addition, the association found in our study suggests a dose-response relationship.…”
Section: Discussionsupporting
confidence: 91%
“…According to the European Food Safety Authority (EFSA), adolescents have an increased chance of sleep latency and reduced sleep duration when consuming 1.4 mg/kg bodyweight of caffeine [ 12 ]. Indeed, the study by Mathew et al showed that on the days that adolescents consumed caffeinated beverages they had a more variable sleep duration and timing of sleep [ 13 ].…”
mentioning
confidence: 99%
“…The animal studies above suggest that this may be primarily due to a shift in sleep onset with no opportunity to compensate by 'sleeping in', rather than an effect of caffeine on sleep quality. A delayed onset of sleep and REM sleep is consistently observed in human studies of caffeine [11], but laboratory studies with EEG have found that chronic stable caffeine use has no effect on sleep architecture or perceived sleep quality [12].…”
Section: Sleep and Brain Blood Flow In Humansmentioning
confidence: 99%
“…These are for example unhealthy food choices, as described in the paper by Al Khatib et al (high non-milk extrinsic sugars and low fibre intake), but also by others (12)(13)(14)(15) . Additionally, social jetlag is associated with high caffeine intake in teenagers (16) . In addition to poorer food choices, social jetlag is thought to increase sedentary behaviours as shown in our own small cross-sectional study, in which those with social jetlag had lower physical activity levels (17) , confirmed by Alves et al (18) Moreover, in addition to decreasing physical activity, an increase in other sedentary behaviours, such as gaming was observed (19) .…”
mentioning
confidence: 99%